Pedagogical Compatibility As A Contemporary Problem - Topuzyan, Aida (Զանգակ հրատ.)
One of the main problems of contemporary pedagogy is the necessity to consider pedagogical compatibility from a valeological point of view. It dictates to study the problem of interaction between the teacher and the learner, affect one another's physical and psychological health and maintaining one another's health in the pedagogical process.The article is based on the results of our questionnaire surveys, conversations among teachers, students, and their parents. The surveys revealed that in some schools still persists the teacher’s authoritarianism and intolerance towards pupils. While organizing the pedagogical process, only a small part of teachers emphasized the health requirements of the lesson, most of them did not pay attention to the problem of pedagogical compatibility, in particular, the process of interaction between the student and teacher was not considered from the point of view of the health of both. However, the majority of teachers realize that the quality of their pupils' education, the effectiveness of their work, the motivation of children towards education, ensuring of their creativity and safety at school largely depends on it. Thus, the question was raised that in the processes of professional education and advanced training of teachers to seriously discuss this problem and provide relevant pieces of knowledge and competencies to the beneficiaries. All of this has prompted the need to enrich the theory of the term “Pedagogical compatibility” and develop a methodological system for its practical implementation. The article defines the essence of the new term “Pedagogical compatibility for health protection”. The principles, methods, the pedagogical conditions necessary for its implementation, the model of competences the teacher needs in this field are presented.
Keywords: Pedagogy